Adulteration Practices of Psychoactive Illicit Drugs: An Updated Review - Solimini, Renata; C. Rotolo, Maria; Pellegrini, Manuela; Minutillo, Adele; Pacifici, Roberta; P. Busardò, Francesco; Zaami, Simona (Current Pharmaceutical Biotechnology, 2017)
Background: Powdery drugs such as cocaine and heroin are frequently adulterated or diluted predominantly to obtain more doses and to increase the drug dealer's profits, but also to enhance, to modify or to oppose drug effects. The aim of this report is to provide an overview of the recent scientific literature on medicines as well as on new psychoactive substances, used as cutting agents (i.e. pharmacologically active adulterants) and on the related adverse health effects on consumers, possibly due to the synergistic effect of the adulterants laced with substances of abuse. Method: A literature search up to January 2017 was performed on MEDLINE, Scopus and Web of Science and reports and documents of international agencies or institutions were also searched. Results: Pharmacologically active substances such as: paracetamol, caffeine, dextromethorphan, clenbuterol for heroin; levamisole, phenacetine, lidocaine, hydroxyzine and diltiazem for cocaine; caffeine and phentermine for amphetamine, have been identified over the years. Furthermore, since cocaine and morphine (this latter as a precursor of heroin) are both extracted from natural products, some impurities and minor alkaloids can be present in the final preparation. In this context, it is worth considering that new psychoactive substances are also used as cutting agents. Conclusion: The wide availability of illicit psychotropic drugs is the most serious hazard threatening consumers. Indeed emergency departments are often responsible in evaluating damages caused not only by the base substance, but also by other eventual compounds added to mimic or antagonize drug effects or simply dilute the drug amount, with a possible harmful synergic toxic action.
Keywords: clenbuterol